A Case of Acrodermatitis Continua of Hallopeau Following Chronic Pustular Cheilitis. Issue 1 (March 2016) - Arisi, Mariachiara; Rossi, Maria; Sala, Raffaella; Petrilli, Giulia; Marocolo, Daniela; Ungari, Marco; Facchetti, Fabio; Calzavara-Pinton, Pier
Abstract We describe the case of a young male affected by chronic pustular psoriasis of the lips that remained the only manifestation of acrodermatitis continua of Hallopeau (ACH) for years before the onset of the characteristic hand lesions.